Influence and assessment of mechanical properties on treated P91 steel with normalizing processes. (2020) - Rohit Sai Krishna, A.; Vamshi Krishna, B.; Sashank, T.; Harshith, D.; Subbiah, Ram
Abstract: P91 steels are widely used in manufacturing power plant and boiler components because of its high thermal conductivity. The modern day large capacity boilers operates at extreme temperature conditions of 570 °C–800 °C and the pressure ranging from 170 bar to 230 bar. So the materials used for these conditions need to have extra ordinary and highly desired properties to extend its applications. In the present experimental investigation, P91 steels were subjected to normalizing process. The analysis is made by varying the time of exposure to heat treatment. The steels are treated to constant temperature and with 3 different timing parameters 60, 90 and 120 min respectively. Mechanical properties like hardness, wear resistance were tested before and after the treatment process. Pin on disc wear studies were carried out at constant speed and load. Finally the surface morphology results were studied with scanning electron microscopic analysis.